2018
DOI: 10.1038/s41419-018-0635-5
|View full text |Cite
|
Sign up to set email alerts
|

A new inhibitor of glucose-6-phosphate dehydrogenase blocks pentose phosphate pathway and suppresses malignant proliferation and metastasis in vivo

Abstract: Pentose phosphate pathway (PPP) is a major glucose metabolism pathway, which has a fundamental role in cancer growth and metastasis. Even though PPP blockade has been pointed out as a very promising strategy against cancer, effective anti-PPP agents are not still available in the clinical setting. Here we demonstrate that the natural molecule polydatin inhibits glucose-6-phosphate dehydrogenase (G6PD), the key enzyme of PPP. Polydatin blocks G6PD causing accumulation of reactive oxygen species and strong incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 47 publications
4
125
0
2
Order By: Relevance
“…In a previous study conducted in our laboratory, we found that G6PD overexpression promoted RCC cell proliferation and tumorigenesis through the positive feedback regulation of p-STAT3 (16). A recent study demonstrated that the blockade of G6PD by polydatin not only leads to cell cycle arrest and cell apoptosis, but also inhibits tumor cell invasion, reduces tumor size and inhibits lymph node metastasis, indicating therefore the crucial role of G6PD in tumor progression (50). Furthermore, the G6PD/hypoxia-inducing factor 1α pathway has been implicated in the nuclear factor-erythroid 2-related factor 2-mediated breast cancer migration (48).…”
Section: Discussionmentioning
confidence: 76%
“…In a previous study conducted in our laboratory, we found that G6PD overexpression promoted RCC cell proliferation and tumorigenesis through the positive feedback regulation of p-STAT3 (16). A recent study demonstrated that the blockade of G6PD by polydatin not only leads to cell cycle arrest and cell apoptosis, but also inhibits tumor cell invasion, reduces tumor size and inhibits lymph node metastasis, indicating therefore the crucial role of G6PD in tumor progression (50). Furthermore, the G6PD/hypoxia-inducing factor 1α pathway has been implicated in the nuclear factor-erythroid 2-related factor 2-mediated breast cancer migration (48).…”
Section: Discussionmentioning
confidence: 76%
“…Samples were then subjected to reduction, alkylation and overnight trypsinisation, following which they were dried down at 60°C for 4 h and stored at 80°C before resuspension in LCMS grade 5% acetonitrile in 0.1% formic acid for subsequent analysis. Analysis by mass spectrometry was performed on a SCIEX TripleTOF 6600 instrument as previously described [22]. Briefly, samples were analysed in both SWATH (Data Independent Acquisition) and IDA (Information Dependent Acquisition) modes for quantitation and spectral library generation respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were then subjected to reduction, alkylation and overnight trypsinisation following which they were dried down at 60°C for 4 h and stored at 80°C before resuspension in LCMS grade 5% acetonitrile in 0.1% formic acid for subsequent analysis. Analysis by mass spectrometry was carried out as previously described on a SCIEX TripleTOF 6600 instrument [12]. Briefly, samples were analysed in both SWATH (Data Independent Acquisition) and IDA (Information Dependent Acquisition) modes for quantitation and spectral library generation respectively.…”
Section: Methodsmentioning
confidence: 99%